1989
DOI: 10.1097/00007890-198906000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Rhesus Immunization From Rh-Incompatible Blood Transfusions During Liver and Heart Transplant Surgery

Abstract: Transfusion of one unit or more of Rh-positive red blood cells normally causes circulating anti-D antibody to appear 2-6 months later in 80-95% of Rh- persons. We asked whether transplant immunosuppression with cyclosporine and corticosteroids affects Rh immunization. Nineteen Rh- liver, heart, and heart-lung transplant recipients received 3-153 (median: 10) units of Rh+ RBCs at surgery and were tested for anti-D greater than 2 months later. Three patients developed anti-D at 11-15 days; one may have had an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…Most other studies reported seroconversion rates between 9.5 and 33% with mean follow-up periods of 14-74 days [9,11,12,14]. Since most multiple injured patients are not immunosuppressed per se, anti-D formation is to be expected more often than in patients with bone marrow transplants or sepsis [26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Most other studies reported seroconversion rates between 9.5 and 33% with mean follow-up periods of 14-74 days [9,11,12,14]. Since most multiple injured patients are not immunosuppressed per se, anti-D formation is to be expected more often than in patients with bone marrow transplants or sepsis [26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…However, we unequivocally excluded any previous exposure to D (Table 1). In addition, primary anti‐D responses have been observed to occur within 2 weeks 15,16 . The medical history of the recipient may include an autoimmune disorder that could have contributed to his rapid immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in another study we have found that primary anti-D formation was detected infrequently after multiple Rh-incompatible RBC transfusions in organ transplant patients. 18 Some of these posttransplant antibodies may have been detected elsewhere previously and subsequently lost before transplant. Hence, the availability of information from the referring hospital would be desirable.…”
Section: Discussionmentioning
confidence: 99%